Composite hydrogen storage material of PdFe double-element mixed monatomic catalyst and MgH2 and preparation method of composite hydrogen storage material

By distributing PdFe bi-element catalyst on the MgH2 surface, the hydrogenation reaction rate and cycle stability of solid hydrogen storage materials are improved, and the temperature and kinetic performance of traditional solid hydrogen storage materials are solved, thereby achieving low-temperature dehydrogenation and high-efficiency hydrogen storage.

CN119160857APending Publication Date: 2024-12-20CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411086803.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing solid hydrogen storage materials have problems such as low hydrogen absorption and discharge rate, poor cycle stability, and high reaction temperature in terms of temperature and kinetic properties, which limit their widespread promotion and application in practical applications.

Method used

A composite hydrogen storage material with PdFe bi-element mixed single-atom catalyst and MgH2 was prepared by ball milling and ultrasonic methods to increase the distribution of the catalyst on the MgH2 surface, improve the hydrogenation reaction rate and efficiency, and achieve dehydrogenation under low temperature conditions.

Benefits of technology

It significantly improves the hydrogen absorption and release kinetic properties of hydrogen storage materials, enhances the hydrogenation reaction rate and cycle stability, and reduces the reaction temperature. It is suitable for large-scale preparation and mobile applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160857A_ABST
    Figure CN119160857A_ABST
Patent Text Reader

Abstract

The invention discloses a composite hydrogen storage material of a PdFe double-element mixed monatomic catalyst and MgH2 and a preparation method, and the preparation method comprises the following steps: adding the PdFe double-element mixed monatomic catalyst into a solvent, uniformly mixing, then adding ball-milled magnesium hydride, and carrying out ultrasonic treatment, stirring and drying to obtain the composite hydrogen storage material of the PdFe double-element mixed monatomic catalyst. The PdFe double-element mixed monatomic catalyst and MgH2 composite hydrogen storage material is obtained. The hydrogen absorption and desorption dynamic performance of the hydrogen storage material can be effectively improved, the hydrogen storage rate, the hydrogen absorption and desorption performance, the cycle stability and the good hydrogen storage reversibility are improved, and the composite hydrogen storage material has considerable hydrogen absorption and storage capacity and rapid hydrogen absorption dynamics, has obvious advantages in practical application, and is suitable for industrial production. Therefore, further development and application of a solid hydrogen storage technology are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of novel solid hydrogen storage materials, and in particular relates to a composite hydrogen storage material of a PdFe dual-element mixed single-atom catalyst and MgH2 and a preparation method thereof. Background Art

[0002] The development of renewable energy and clean energy technologies has become particularly urgent. However, renewable energy sources such as solar and wind energy are intermittent and unstable, so efficient energy conversion and storage technologies are needed to solve the problem of energy supply and demand imbalance. Solid hydrogen storage technology, as an important energy conversion and storage technology, has the advantages of high hydrogen storage density, relatively low hydrogen storage pressure, and zero emissions. It is widely regarded as one of the effective ways to promote the use of renewable energy.

[0003] Traditional solid hydrogen storage materials mainly include magnesium-based, lithium-based, sodium-based and other materials. Solid hydrogen storage materials have the following advantages:

[0004] High volumetric hydrogen storage density: Solid hydrogen storage materials have a much higher volumetric hydrogen storage density than liquid hydrogen and gaseous hydrogen. Taking MgH2 as an example, its volumetric hydrogen storage density can reach 106kg·m 3 , which is 119 times the density of hydrogen under standard conditions, 2.7 times that of 70MPa high-pressure hydrogen storage, and 1.5 times that of liquid hydrogen.

[0005] Good safety: Solid hydrogen storage materials are relatively stable at room temperature and pressure, and do not require high pressure or low temperature conditions, reducing the risk of hydrogen leakage and explosion. Solid hydrogen storage can be carried out at room temperature and pressure, and the storage tank is easy to seal. Even if hydrogen leakage occurs in an emergency, the storage tank can automatically reduce the hydrogen leakage speed and leakage amount, buying precious time for taking safety measures.

[0006] Good long-term cycle stability: Certain solid hydrogen storage materials have excellent hydrogen absorption and desorption properties and the advantages of no kinetic decay and capacity loss in long-term cycles. They can achieve large-capacity solid-state hydrogen storage, which is beneficial to the long-term storage and recycling of hydrogen.

[0007] Low hydrogen storage pressure: Solid hydrogen storage materials usually do not require high pressure conditions to store hydrogen, reducing the complexity and cost of hydrogen storage equipment.

[0008] High purity of hydrogen desorption: During the desorption process, solid hydrogen storage materials can usually produce higher purity hydrogen due to the better controllability of the reaction, meeting the needs of specific applications.

[0009] Rich resources and low cost: Solid hydrogen storage materials, such as magnesium-based hydrogen storage materials, whose raw material magnesium is one of the abundant elements in the earth's crust, are abundant in resources and low in price, which is conducive to reducing the cost of hydrogen storage.

[0010] Environmentally friendly: Solid hydrogen storage materials usually do not produce harmful substances during the process of absorbing and releasing hydrogen, which is in line with the green and environmentally friendly development concept.

[0011] Among them, magnesium-based hydrogen storage materials have attracted much attention due to their abundant resources, good renewability and high theoretical hydrogen storage capacity.

[0012] However, existing solid hydrogen storage materials have some challenges in terms of temperature and kinetic performance, such as low hydrogen absorption and desorption rates, poor cycle stability, and high reaction temperature, which lead to the following disadvantages, thus restricting their widespread promotion and application in practical applications.

[0013] 1. Energy consumption: High reaction temperature usually requires more energy to heat or maintain, which increases the energy consumption of hydrogen storage and release processes.

[0014] 2. Safety: High temperature environment may cause material instability and increase safety risks, such as thermal decomposition, combustion or explosion of materials.

[0015] 3. Shortened lifespan: High temperature may accelerate the degradation or aging process of the material and shorten the service life of the solid hydrogen storage material.

[0016] 4. Limited practicality: High reaction temperature limits the use of solid hydrogen storage materials in mobile applications (such as automobiles) because it is difficult to provide a continuous high temperature environment in mobile applications.

[0017] Catalysts play a vital role in solid hydrogen storage reactions. They can regulate the kinetics of hydrogen storage reactions, reduce the activation energy of reactions, and increase hydrogen storage rates and cycle stability. However, the application of traditional catalysts in the field of solid hydrogen storage is limited, and their catalytic effect and stability need to be further improved. Summary of the invention

[0018] In order to overcome the problems of high dehydrogenation temperature and slow dehydrogenation kinetics of traditional bulk MgH2, the purpose of the present invention is to provide a composite hydrogen storage material of PdFe dual-element mixed single-atom catalyst and MgH2 and a preparation method. The material may provide more active sites, enhance the rate and efficiency of the hydrogenation reaction, and have stronger interaction and synergistic effects in the catalytic reaction, thereby achieving low-temperature dehydrogenation.

[0019] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0020] One aspect of the present invention provides a method for preparing a composite hydrogen storage material of a PdFe dual-element mixed single-atom catalyst and MgH2, comprising the following steps:

[0021] The PdFe dual-element mixed single-atom catalyst is added to the solvent and mixed evenly, and then ball-milled magnesium hydride is added, ultrasonicated, stirred, and dried to obtain a composite hydrogen storage material of the PdFe dual-element mixed single-atom catalyst and MgH2.

[0022] The present invention is further preferred in that the PdFe dual-element mixed single-atom catalyst is 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride.

[0023] It is further preferred in the present invention that the solvent is tetrahydrofuran, N,N-dimethylformamide or N,N-dimethylacetamide.

[0024] The present invention is further preferred in that the mass ratio of 1,1'-bis(diphenylphosphinoferrocene)palladium dichloride to ball-milled magnesium hydride is 1:4-5.

[0025] The present invention is further preferred in that the mass ratio of 1,1'-bis(diphenylphosphinoferrocene)palladium dichloride to the solvent is 1:19-20.

[0026] The present invention is further preferred in that the ball-milled magnesium hydride is prepared by the following process: adding MgH2 to tetrahydrofuran, ball-milling in forward and reverse directions, and drying to obtain the ball-milled magnesium hydride.

[0027] The present invention is further preferred in that the specific process of forward and reverse ball milling is: forward ball milling for 20 minutes, stop for 10 minutes, reverse ball milling for 20 minutes, stop for 10 minutes, the total ball milling time is 6 hours, and the ball milling speed is 500 rpm.

[0028] The present invention is further preferred in that the drying condition is: vacuum drying at 60-65° C. for 2-3 hours.

[0029] Another aspect of the present invention provides a composite hydrogen storage material of a PdFe dual-element mixed single-atom catalyst and MgH2.

[0030] Furthermore, the composite hydrogen storage material has a hydrogen storage density of 5.9 wt% under the conditions of a hydrogen pressure of 3 MPa and a temperature of 250°C;

[0031] The composite hydrogen storage material has a hydrogen storage density of 6.5 wt % under the conditions of a hydrogen pressure of 3 MPa and a temperature of 350° C.

[0032] Compared with the prior art, the solid hydrogen storage material of the present invention has the following beneficial effects:

[0033] The present invention adopts PdFe dual-element mixed single-atom catalyst and MgH2 to prepare a new composite hydrogen storage material. Compared with the single-atom catalyst, the dual-atom catalyst described in the present invention may provide more active sites, enhance the rate and efficiency of the hydrogenation reaction, and have stronger interaction and synergistic effects in the catalytic reaction. The presence of the PdFe dual-element mixed single-atom catalyst reduces the agglomeration of MgH2 particles during hydrogen absorption and dehydrogenation, and can effectively improve the hydrogen absorption and desorption kinetics of the hydrogen storage material, improve the hydrogen storage rate, hydrogen absorption and desorption performance and cycle stability, and good hydrogen storage reversibility. The composite hydrogen storage material of the present invention has a relatively considerable adsorption hydrogen storage capacity and fast hydrogen adsorption kinetics, which has obvious advantages in practical applications, thereby promoting the further development and application of solid hydrogen storage technology. The method is simple to operate, mild conditions, and is suitable for large-scale preparation.

[0034] Furthermore, when ball-milling magnesium hydride is prepared, a PdFe dual-element mixed single-atom catalyst is distributed on the surface of MgH2 after ball milling, which increases the number of active sites for hydrogen absorption and desorption and promotes the dissociation and recombination of hydrogen molecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 The hydrogenation curves of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention at different temperatures;

[0037] Figure 2 Dehydrogenation curves at different temperatures of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention;

[0038] Figure 3 This is the dehydrogenation curve of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention under low temperature test conditions;

[0039] Figure 4 The scanning electron microscope images of the MgH2-5wt% PdFe composite hydrogen storage material obtained in Example 1 of the present invention at different magnifications; wherein (a) is at a magnification of 5.51k, (b) is at a magnification of 10.9k, and (c) is at a magnification of 28.6k;

[0040] Figure 5The scanning electron microscope images of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention after three cycles at different magnifications; wherein (a) is at a magnification of 4.33k, (b) is at a magnification of 10.4k, and (c) is at a magnification of 25.2k;

[0041] Figure 6 XRD diagram of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention and the sample after three cycles;

[0042] Figure 7 TEM images of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention after three cycles and elemental images of Mg, Fe, Cl, P, and Pd; wherein (a) is a TEM image, (b) is the element Mg, (c) is the element Fe, (d) is the element Cl, (e) is the element P, and (f) is the element Pd;

[0043] Figure 8 TEM images of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention after three cycles at different magnifications; wherein (a) is at a magnification of 86k, (b) is at a magnification of 370k, and (c) is at a magnification of 3800k;

[0044] Fig. 9 This is the SAED diagram of the MgH2-5wt%PdFe composite hydrogen storage material obtained in Example 1 of the present invention after three cycles;

[0045] Fig.10 This is a STEM image of the MgH2-5wt% PdFe composite hydrogen storage material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0046] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0047] Those skilled in the art should understand that in the following description of the embodiments of the present invention, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.

[0048] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "an" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0049] It will be appreciated by those skilled in the art that the numerical ranges in the embodiments of the present invention are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the range. Each smaller range between the intermediate values ​​in any stated value and stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.

[0050] In the following description, reference is made to "some embodiments", which describe a subset of all possible embodiments, but it is understood that "some embodiments" may be the same subset or different subsets of all possible embodiments, and may be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present invention have the same meaning as those commonly understood by those skilled in the art to which the embodiments of the present invention pertain. The terms used in the embodiments of the present invention are only for the purpose of describing the embodiments of the present invention and are not intended to limit the present invention.

[0051] As a new type of catalyst material, PdFe diatomic catalyst has good catalytic activity and selectivity, and can play an important role in solid hydrogen storage reactions. PdFe diatomic catalyst can significantly improve the hydrogen absorption and desorption performance of solid hydrogen storage materials and promote the hydrogen storage reaction by regulating the surface hydrogen atom adsorption energy and the generation of reaction intermediates. The composite hydrogen storage material in the present invention can effectively improve the hydrogen absorption and desorption kinetics of hydrogen storage materials by combining the catalyst with the hydrogen storage material, improve the hydrogen storage rate, hydrogen absorption and desorption performance and cycle stability, thereby promoting the further development and application of solid hydrogen storage technology.

[0052] In some embodiments of the present invention, the preparation method of the composite hydrogen storage material of PdFe dual element mixed single atom catalyst and MgH2 comprises the following steps:

[0053] Preparation of ball-milled magnesium hydride: Add 2g MgH2 to 5mL THF and use SMF-1 planetary ball mill for ball milling. During the ball milling process, each forward ball milling for 20min, stop for 10min, then reverse ball milling for 20min, stop for 10min, the total ball milling time is 6h. The ball milling speed is 500rpm. Finally, dry at 60℃ for 2h in a vacuum oven in the glove box, take out the sample, and obtain ball-milled magnesium hydride. After ball milling, magnesium hydride forms irregular micron-sized particles, which is conducive to the distribution of PdFe diatomic catalyst on the surface of MgH2.

[0054] 1,1'-bis(diphenylphosphinoferrocenepalladium(II) chloride (C 34 H 28 Cl2FeP2Pd) is added to a solvent (the solvent can be THF tetrahydrofuran, Tetrahydrofuran) and N,N-dimethylformamide (DMF, N,N-Dimethylformamide) or N,N-dimethylacetamide (DMAC, Dimethylacetamide) is selected to make the solution dispersed evenly. The dispersed solution is added to BM-MgH2 ultrasonically, and finally stirred and dried to obtain a composite hydrogen storage material of PdFe dual-element mixed single-atom catalyst and MgH2, which is recorded as MgH2-PdFe.

[0055] Among them, 1,1'-bis(diphenylphosphinoferrocene)palladium dichloride is the PdFe dual-element mixed single-atom catalyst.

[0056] The mass ratio of 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride to BM-MgH2 is 1:4-5.

[0057] 1,1'-Bis(diphenylphosphino)ferrocenepalladium(II) chloride 34 H 28 The mass ratio of Cl2FeP2Pd) to the solvent is 1:19-20.

[0058] Some embodiments The composite hydrogen storage material prepared by the present invention achieves a hydrogen storage density of 5.9 wt % under the conditions of a hydrogen pressure of 3 MPa and a temperature of 250° C.

[0059] Some embodiments The composite hydrogen storage material prepared by the present invention achieves a hydrogen storage density of 6.5 wt % under the conditions of a hydrogen pressure of 3 MPa and a temperature of 350° C. It can be seen that the composite hydrogen storage material has a characteristic of having a higher hydrogen storage density as the temperature increases.

[0060] Example 1

[0061] The preparation method of the MgH2-5wt%PdFe composite hydrogen storage material of the present invention comprises the following steps:

[0062] 1) 50 mg of 1,1'-bis(diphenylphosphinoferrocene)palladium dichloride (C 34 H 28 Cl2FeP2Pd) was added with 1 mL of THF to disperse the solution evenly to obtain a solution with a concentration of 5 wt%.

[0063] 2) Add 200 mg BM-MgH2 to the solution and sonicate for 30 min.

[0064] 3) After the ultrasonic treatment is completed, the sample is stirred for 12 hours and dried in a vacuum oven to obtain a composite hydrogen storage material of PdFe dual-element mixed single-atom catalyst and MgH2, namely, MgH2-5wt% PdFe composite hydrogen storage material.

[0065] Example 2

[0066] The method for preparing the composite hydrogen storage material of the present invention comprises the following steps:

[0067] 1) 50 mg of 1,1'-bis(diphenylphosphinoferrocene)palladium dichloride (C 34 H 28 Cl2FeP2Pd) was added with 0.95 mL of N,N-dimethylformamide to disperse the solution uniformly to obtain a solution.

[0068] 2) Add 250 mg BM-MgH2 to the solution and sonicate for 30 min.

[0069] 3) After the ultrasonic treatment is completed, the sample is stirred for 12 hours and dried in a vacuum oven to obtain a composite hydrogen storage material of PdFe dual-element mixed single atom catalyst and MgH2.

[0070] Example 3

[0071] The method for preparing the composite hydrogen storage material of the present invention comprises the following steps:

[0072] 1) 50 mg of 1,1'-bis(diphenylphosphinoferrocene)palladium dichloride (C 34 H 28 Cl2FeP2Pd) was added with 0.97 mL of N,N-dimethylacetamide to disperse the solution uniformly to obtain a solution.

[0073] 2) Add 220 mg BM-MgH2 to the solution and sonicate for 30 min.

[0074] 3) After the ultrasonic treatment is completed, the sample is stirred for 12 hours and dried in a vacuum oven to obtain a composite hydrogen storage material of PdFe dual-element mixed single atom catalyst and MgH2.

[0075] Example 4

[0076] The method for preparing the composite hydrogen storage material of the present invention comprises the following steps:

[0077] 1) 50 mg of 1,1'-bis(diphenylphosphinoferrocene)palladium dichloride (C 34 H 28 Cl2FeP2Pd) was added with 0.98 mL of N,N-dimethylacetamide to disperse the solution uniformly to obtain a solution.

[0078] 2) Add 240 mg BM-MgH2 to the solution and sonicate for 30 min.

[0079] 3) After the ultrasonic treatment is completed, the sample is stirred for 12 hours and dried in a vacuum oven to obtain a composite hydrogen storage material of PdFe dual-element mixed single atom catalyst and MgH2.

[0080] The structural characteristics and hydrogen storage performance of the MgH2-5wt%PdFe composite hydrogen storage material prepared in Example 1 are described below in conjunction with the accompanying drawings.

[0081] Figure 1 The kinetic test results of hydrogen isobaric adsorption of MgH2-5wt%PdFe are shown, and the test temperatures are 250°C, 300°C and 350°C. Among them, the hydrogen adsorption amount obtained by testing at 250°C is 5.9wt%; the hydrogen adsorption amount obtained by testing at 300°C is 6.1wt%; and the hydrogen adsorption amount obtained by testing at 350°C is 6.5wt%, which proves that the composite hydrogen storage material has the characteristic of higher hydrogen storage density as the temperature increases.

[0082] Figure 2-Figure 3 The results of the dehydrogenation kinetics test of MgH2-5wt% PdFe are shown. The test temperatures are 250℃, 300℃ and 350℃, and the corresponding dehydrogenation amounts are 4.52wt%, 5.78wt% and 6.32wt%, respectively, proving that the composite hydrogen storage material has good cycle performance. It can be seen that the composite hydrogen storage material presents irregular particles, and the hydrogen cycle process does not destroy the morphology of the sample.

[0083] Figure 4-Figure 5 The scanning electron microscope images of different magnifications of the MgH2-5wt%PdFe composite hydrogen storage material and the composite hydrogen storage material after three cycles are shown respectively. Figure 4 In (a), (b) and (c), it can be seen that the ground MgH2-5wt%PdFe sample presents irregular micron-sized particles.

[0084] from Figure 5 In (a), (b) and (c), it can be seen that after dehydrogenation and hydrogenation, the PdFe catalyst particles aggregate and expand.

[0085] Figure 6 The XRD images of the MgH2-5wt% PdFe composite hydrogen storage material and after three cycles are shown. The composite hydrogen storage material only produces a small amount of Mg after three cycles, proving that the composite hydrogen storage material has good hydrogen storage reversibility and the crystallinity of the MgH2 crystals is better after the cycle.

[0086] Figure 7(a)-(f) show the TEM images of the MgH2-5wt% PdFe composite hydrogen storage material after three cycles and the elemental diagrams of Mg, Fe, Cl, P, and Pd, indicating that the Mg, Fe, Cl, P, and Pd elements are uniformly distributed in the entire composite hydrogen storage material, and the PdFe diatomic catalyst is in full contact with MgH2.

[0087] Figure 8 TEM images of the MgH2-5wt%PdFe composite hydrogen storage material at different magnifications after three cycles are shown. Figure 8 (a) and Figure 8 (b) shows the lamellar structure of the sample. Figure 8 The interplanar spacings of 0.2075 nm and 0.2086 nm shown in (c) correspond to the (102) plane of Mg, and 0.2147 nm and 0.2108 nm correspond to the (200) plane of MgH2.

[0088] Fig. 9 The SAED pattern of the MgH2-5wt%PdFe composite hydrogen storage material after three cycles is shown. From the diffraction rings shown in the figure, the interplanar spacings of 0.01527nm and 0.2158nm can be obtained, which are derived from the (103) crystal plane of the Mg crystal and the (200) crystal plane of the MgH2 crystal, respectively.

[0089] Fig.10 The spherical aberration corrected electron microscope image of the MgH2-5wt%PdFe composite hydrogen storage material is shown, from which it can be seen that atomic-level catalysts are dispersed on the MgH2 carrier, among which the brighter ones are palladium atoms and the relatively darker ones are iron atoms, thereby proving that the catalyst used in the present invention is a single-atom catalyst.

[0090] The present invention can change the type and ratio of the diatomic catalyst to obtain composite hydrogen storage materials of different diatomic catalysts and MgH2, all of which can achieve good near-room temperature and high-temperature hydrogen storage performance.

[0091] The present invention has the following advantages:

[0092] 1) This method is simple to operate, has mild conditions, and is suitable for large-scale preparation;

[0093] 2) The MgH2-PdFe prepared by the present invention has a relatively considerable adsorption hydrogen storage capacity and fast hydrogen adsorption kinetics, which has obvious advantages in practical applications. During the ball milling process, the catalyst is distributed on the surface of MgH2, increasing the number of active sites for hydrogen absorption and desorption, and promoting the dissociation and recombination of hydrogen molecules. In addition, the presence of the PdFe diatomic catalyst reduces the agglomeration of MgH2 particles during hydrogen absorption and dehydrogenation.

[0094] 3) The present invention uses PdFe diatomic catalyst and MgH2 to prepare a new composite hydrogen storage material. Compared with single-atom catalysts, the diatomic catalysts described in the present invention may provide more active sites, enhance the rate and efficiency of hydrogenation reactions, and have stronger interactions and synergistic effects in catalytic reactions.

[0095] It should be noted that all raw materials and / or reagents in the examples of the present invention are purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0096] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0097] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. PdFe dual element mixed single atom catalyst and MgH 2 Preparation method of composite hydrogen storage material, It is characterized in that The following steps are involved: The PdFe dual-element mixed single-atom catalyst was added to the solvent and mixed evenly, and then ball-milled magnesium hydride was added, ultrasonicated, stirred, and dried to obtain the PdFe dual-element mixed single-atom catalyst and MgH 2 Composite hydrogen storage materials.

2. The PdFe dual element mixed single atom catalyst and MgH according to claim 1 2 Preparation method of composite hydrogen storage material, It is characterized in that The PdFe dual-element mixed single-atom catalyst is 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride.

3. The PdFe dual element mixed single atom catalyst and MgH 2 Preparation method of composite hydrogen storage material, It is characterized in that The solvent is tetrahydrofuran, N,N-dimethylformamide or N,N-dimethylacetamide.

4. The PdFe dual element mixed single atom catalyst and MgH according to claim 1 2 Preparation method of composite hydrogen storage material, It is characterized in that The mass ratio of 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride to ball-milled magnesium hydride is 1:4-5.

5. The PdFe dual element mixed single atom catalyst and MgH according to claim 1 2 Preparation method of composite hydrogen storage material, It is characterized in that The mass ratio of 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride to the solvent is 1:19-20.

6. The PdFe dual element mixed single atom catalyst and MgH according to claim 1 2 Preparation method of composite hydrogen storage material, It is characterized in that Ball-milled magnesium hydride is prepared by the following process: MgH 2 Add into tetrahydrofuran, perform forward and reverse ball milling, and dry to obtain ball-milled magnesium hydride.

7. The PdFe dual element mixed single atom catalyst and MgH according to claim 1 2 Preparation method of composite hydrogen storage material, It is characterized in that The specific process of forward and reverse ball milling is: forward ball milling for 20 minutes, stop for 10 minutes, reverse ball milling for 20 minutes, stop for 10 minutes, the total ball milling time is 6 hours, and the ball milling speed is 500 rpm.

8. The PdFe dual element mixed single atom catalyst and MgH according to claim 1 2 Preparation method of composite hydrogen storage material, It is characterized in that The drying conditions are: vacuum drying at 60-65°C for 2-3h.

9. A PdFe dual-element mixed single-atom catalyst and MgH prepared by the method according to any one of claims 1 to 8 2 Composite hydrogen storage materials.

10. The PdFe dual element mixed single atom catalyst and MgH according to claim 9 2 Composite hydrogen storage materials It is characterized in that The composite hydrogen storage material has a hydrogen storage density of 5.9wt% under the conditions of a hydrogen pressure of 3MPa and a temperature of 250°C; The composite hydrogen storage material has a hydrogen storage density of 6.5 wt % under the conditions of a hydrogen pressure of 3 MPa and a temperature of 350° C.